The Royal College of Psychiatrists Child and Adolescent Psychiatry Surveillance System for rare events and disorders: highlighting the need for an international network for surveillance - Muthukrishnan Venkatesan; Eleanor Smith; Marinos Kyriakopoulos; Aditya Narain Sharma (BJPsych International)
Commonly occurring mental health disorders have been well studied in terms of epidemiology, presentation, risk factors and management. However, rare or uncommon mental health disorders and events are harder to study. One way to do this is active surveillance. This article summarises how the Royal College of Psychiatrists Child and Adolescent Psychiatry Surveillance System was developed, as well as the key studies that have used the system and their impact, to make the case for a wider international surveillance unit for child and adolescent psychiatry. Keeping this surveillance active in different populations across the globe will add to existing knowledge and understanding of these uncommon disorders and events. This will in turn help in developing better frameworks for the identification and management for these disorders and events. It will also facilitate the sharing of ideas regarding current methodology, ethics, the most appropriate means of evaluating units and their potential applications.